Enhanced Educational Mobile Augmented Reality Application for Musculoskeletal System and Warm-Up Exercises - Imamoglu, Mehmet (Asian Journal of Contemporary Education, 2020)
The purpose of this study is to examine the use of augmented reality technology in the field of sports science and to develop a sample educational software including musculoskeletal system and warm-up exercises. Each stage of the software development process is explained in detail. The basis of augmented reality technology is the simultaneous visualization of real and virtual objects through an interface system. The instant information obtained by using various methods from the real world is presented in interaction with virtual objects. Virtual objects are developed with three-dimensional modelling software. Code libraries are used for applications that will be created for products such as mobile phones, tablets, and computers. The compiler software makes applications available for use. In this study, Daz3d and Blender software were used for three-dimensional modelling. The Vuforia system has been preferred as an augmented reality code library. The Unity software was used in the development and compilation of the application. It will be beneficial to use the developed mobile augmented reality application in sports and health education. Augmented reality technology can be used in many different areas in sports science.